Assessment of HLADP gene rs3128917 and rs9380343 polymorphisms in chronic HBV infection - Ersin Akgöllü (Turkish Journal of Gastroenterology, 2019)
Background/Aims: About 400 million people worldwide have been exposed to Hepatitis B (HBV) infection. A range of 10%-15% of chronic HBV carriers may present with various liver diseases including cirrhosis and hepatic cancer. The chronicity or clearance of HBV infection is dependent on viral and genetic variables. Genome-wide association studies (GWAS) have reported that the variants of human leukocyte antigen (HLA), rs3128917 and rs9380343, are significantly related to persistent HBV infection. HLA molecules are responsible for introducing various antigens into the immune system. These variants might affect antigen presentation by influencing HLA mRNA expression, therefore, antigen presentation may not be performed properly. This study aims to assess the relationship of HLA gene variants to chronic HBV infection. Materials and Methods: HLA variants were explored in 238 chronic HBV patients and in 238 individuals with spontaneous clearance of HBV using PCR-RFLP assay. Results: The allele and genotype of rs9380343 polymorphism were associated with persistent HBV infection risk (allele: p=0.038, genotype: p=0.029), but rs3128917 polymorphism was not significant. Additionally, rs9380343 polymorphism was also related to increased risk of HBV infection in males (p<0.05). Conclusion: The current study is the first report demonstrating the HLA rs9380343 polymorphism as a genetic risk factor for chronicity of HBV infection. Further independent studies are required to confirm the current findings using a larger sample size in different populations. Cite this article as: Akgöllü E. Assessment of HLADP Gene rs3128917 and rs9380343 Polymorphisms in Chronic HBV Infection. Turk J Gastroenterol 2019; 30(7): 616-23.